Sulfamethoxazole/trimethoprim versus fluoroquinolones for the treatment of Stenotrophomonas maltophilia bloodstream infections. (March 2018) - Watson, Lucas; Esterly, John; Jensen, Ashley O.; Postelnick, Michael; Aguirre, Arturo; McLaughlin, Milena
Highlights: Stenotrophomonas maltophilia is an opportunistic pathogen with intrinsic resistance to several antibiotics. Stenotrophomonas maltophilia frequently presents as nosocomial infections. There are few bloodstream infection outcome studies comparing multiple fluoroquinolones with sulfamethoxazole/trimethoprim. Data from this study suggest the three fluoroquinolones have similar outcomes to sulfamethoxazole/trimethoprim. Abstract: Objectives: Stenotrophomonas maltophilia causes high mortality rates, especially in bloodstream infections (BSIs) where there is a lack of comparative data with fluoroquinolones (FQs) and sulfamethoxazole/trimethoprim (SXT). The objective of this study was to evaluate outcomes in patients with S. maltophilia BSI who were treated with FQs versus SXT. Methods: A retrospective study was conducted to compare FQs (levofloxacin, ciprofloxacin and moxifloxacin) versus SXT for the treatment of S. maltophilia BSI. Results: A total of 54 patients were included in this retrospective study, including 32 treated with SXT and 22 treated with FQs (11 ciprofloxacin, 5 levofloxacin and 6 moxifloxacin). There were 3 deaths (13.6%) in the FQ group versus 10 (31.3%) in the SXT group ( P  = 0.20). Modified Acute Physiology and Chronic Health Evaluation (APACHE) II score [odds ratio (OR) = 1.4, 95% confidence interval (CI) 1.1–1.8] and broad-spectrum antibiotics prior to culture (OR = 8, 95% CI 1.3–49.8) were significant predictors of mortality. Conclusions: Ciprofloxacin, moxifloxacin and levofloxacin are possible alternatives to SXT for S. maltophilia BSI; however, further investigation is needed to confirm these findings.